Hepcidin Deficiency Disrupts Iron Homeostasis and Induces Ferroptosis in Zebrafish Liver - Mingli Liu; Mingjian Peng; Jingwen Ma; Ruiqin Hu; Qianghua Xu; Peng Hu; Liangbiao Chen (Fishes, 2025)
Hepcidin is a key regulator of systemic iron homeostasis, which is essential for maintaining iron balance and cellular health. To investigate its role in zebrafish, we empolyed a hepcidin knockout model. Morphological and histological analyses revealed pale livers and significant iron accumulation in hep−/− zebrafish, particularly in liver, skin, and egg tissues. RNA sequencing identified 1,424 differentially expressed genes (DEGs) between wild-type (WT) and hep−/− zebrafish, with significant enrichment in pathways related to ferroptosis, fatty acid degradation, and heme binding. Western blot analysis showed reduced levels of key iron-related proteins, including GPX4, Fth1, and ferroportin (FPN), indicating impaired iron transport and increased oxidative stress. Gene Ontology (GO) and KEGG analyses highlighted disruptions in iron metabolism and lipid oxidation, linking iron overload to ferroptosis in the absence of hepcidin. These findings demonstrate that hepcidin deficiency leads to profound dysregulation of iron homeostasis, driving lipid peroxidation and ferroptosis in the zebrafish liver. Our study provides mechanistic insights into the molecular consequences of hepcidin loss, advancing our understanding of iron-related oxidative damage and its physiological impacts.